Komunikasi Pemasaran Pariwisata Berbasis Digital (Studi pada Desa Sambangan Kabupaten Buleleng) - A. A. Ngurah Oka Suryadinatha Gorda; Widya Hadi Saputra Widya Hadi Saputra; Ni Putu Yunita Anggreswari (Jayapangus Press, 2020)
Sambangan Village is one of 10 villages designated by the Government of the Regency of Buleleng as a Tourism Village based on the Decree of the Regent of Buleleng number 430/927 / HK / 2015 dated December 21st, 2015. Sambangan Village has good tourism potential to develop including natural waterfalls, the traditional fertility system using terracing models, accommodation facilities (villas and restaurants), spiritual tourism, and tourist attractions (tracking paths, water rides, and camping ground). However, the development of tourism objects in Sambangan Village is not optimal, the number of tourists coming to Buleleng Regency does not necessarily increase tourism visits to Sambangan Village. This is due to lack of marketing and supporting resources. Utilization of digital marketing that is developing at this time has not been done well. The purpose of this study is to analyze the level of visits, marketing models that have been carried out and analyze effective digital-based marketing strategies. The method used in this study is a qualitative approach, data collection using interview and observation techniques, and use triangulation techniques to check the validity of the data. Results from this study indicate that the marketing activities undertaken by Village Sambangan still needs to be improved as well as the need for specialized training for managers of tourist attraction.